Teacher Efforts to Increase Student Learning Activeness in Thematic Learning of Science Materials During the Covid-19 Pandemic Class V SDN 66 Bengkulu City - Rizky, Miranti Nur; Febrini, Deni; Mukti, Wiji Aziiz Hari (PPSDP Undergraduate Journal of Educational Sciences, 2024)
This study aims to determine the teacher’s efforts to increase student learning activeness in thematic learning of science materials during the Covid-19 pandemic for Class V SDN 66 Bengkulu City. The approach in this research is a qualitative approach with the type of Ex Post Facto research. Methods of data collection using observation, interviews, documentation and attachments. The results of the study revealed that: 1) the teacher’s efforts to increase thematic learning activity during the Covid-19 pandemic. In thematic learning during the Covid-19 pandemic using online learning that had been provided by the school using mobile phones. In online learning, students are less active in the learning process because they are a little surprised and bored compared to normal learning, the teacher explains thematic material in online learning, students only pay attention, and take notes with explanations from the teacher without expressing opinions. During normal learning the teacher usually explains the material and holds group discussions with students, in online learning the teacher rarely holds group discussions and immediately gives assignments to do at home without knowing whether the students understand what the teacher explains. 2) the lack of use of various learning methods and media provided by teachers in thematic learning so that students feel bored, sleepy, and do not understand thematic learning during the co-19 pandemic. 3) During the Covid-19 pandemic it was one of the obstacles for teachers and students in the thematic teaching and learning process. Students have influence over friends, who usually study in class with friends and are now only limited through online learning. Student concentration decreases during the day when using morning and afternoon sessions in online learning, students are more enthusiastic and concentrate on learning to start in the morning. During the Covid-19 period, students interacted with friends limited to face-to-face activities, limited to online learning.